Peningkatan Kapasitas Digital Marketing Bagi Pelaku UMKM di Desa Sukamahi - Rismawati, Rismawati; Apriyanti, Vadiah; Sari, Ramsih Rosita; Istiani Putri, Alfia Nur; Maulana, Fajar Arif (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Sukamahi Village in the field of digital marketing. Many MSME actors still rely on conventional marketing methods, which limits their market reach and hinders business development. Through intensive training and mentoring, participants were introduced to digital marketing strategies such as the use of social media, online marketplaces, and the creation of effective promotional content. The results of the activity indicate an improvement in participants' understanding and ability to manage digital marketing. This increased competence is expected to boost the competitiveness and income of MSMEs in the village.